Studi Komparatif Sistem Bagi Hasil Pembiayaan Mudharabah dan Sistem Bunga Kredit Pinjaman - Yanuar, Deni; Rosita, Siti Ita (Jurnal Ilmiah Akuntansi Kesatuan, 2013)
The development of Islamic banking in indonesia is getting better, a lot of banks that finallyopened a subsidiary engaged in the field of sharia or islamic business units. This is because theopening of the eyes of society Indonesia will practice usury in haram banks and conventionalbanking practices that want to locate in the halal In religion views. With this research, it,s expectedtobe made public is more aware of such differences, particlarly regarding concepts for results andinterest.The Research method is qualitative data analysis methods. This analysis aims to find outwhether the system applied by the object of research in accordance with theories that have beenstudied. Awarding of costs of the customer either in financing or in financing credit mudharabahby Bank Syariah X and Bank X not off of the various procedures that have been recorded on thecompany’s manual and various kinds of analysis. With meet procedure credit financingdetermined, the credit financing can work smoothly and can be done in management too. Infunding there are elements that is essential for survival bank. In mudharabah financing, theelements is a benefit sharing (for a results) that is, process benefit-sharing among owner funds andfund management according calneh the agreed. To financing credit, the element called interest,namely additional worn into transactions lending money. There are diffrences in the system for theresults and system interest,of them calneh agreement beginning, profit banks and customer andothers.